East African community and Hutu-Tutsi conflict, 2000-2011 - Abdullah Saidi, Mpawenimana; Ra'ees, Wahabuddin Sahibuddin (IIUM Press, 2017)
This book examines the role of EAC in the Hutu-Tutsi conflict. East African region experienced unprecedented conflict in the region in 1994 fueled by the ethnic politics between Hutu and Tutsi. The scale of the conflict thus necessitated the intervention of the regional organization and other international bodies. This book thus studied the role of EAC regional organization and mechanisms put in place in settling the conflict. The study uses qualitative method of data analysis and uses theory of functionalism as framework for analysis. The study used official documents, group discussion, interview, journal article, memoirs, correspondence and conference papers in collecting the data. The findings of the research reveal that EAC has made a number of achievements which have directly or indirectly contributed to reducing of Hutu-Tutsi conflict in East Africa. The book also found that political federation cannot be achieved in haste and could be a gradual process. The study thus suggests that EAC needs to take its time and put its house in order before projecting the lofty idea of political federation as it is faced with challenges in implementing its policies on trade and commerce as well as socio-political fields. Challenges among others include establishment of common identity to reduce tension among the citizens of EAC in the region and establishment of custom union which could provide detailed policies to harmonize economic policies among EAC member states. This book concludes with making some valuable recommendations. The book recommends that EAC member states must seriously focus on implementing the policies and programmes it has initiated since its establishment.